Homopolar Pulsed Welding of Steel Pipe: Effects of Controlled Parameters on Weld Properties - Trevisan, R.E.; Harville, M.W; Gully, J.H. (1992)
This paper reports on recent and continuing research into the optimization of the homopolar pulsed weld (HPW) process for welding 89-mm diameter, ASTM 1035 steel pipe. Present study characterizes the typical macro- and microstructure found in HPW and seeks to identify causes of low toughness. Metallurgical and mechanical evaluation indicated nonuniform heating around the circumference of the pipe. New electrodes were fabricated and shown to reduce circumferential nonuniformity in the weld specimens, and improve the weld repeatability. Several experiments were performed that varied process control parameters, one at a time, and identified the effects on weld properties. However, the process control parameters investigated did not improve the weld toughness. The reduced toughness at the weld line of the HPW process is attributed to the large grain size present on this region. Center for Electromechanics